Levitin-Polyak Well-posedness by perturbations for bilevel mixed vector variational inequalities - Wei, Wenbin; Jiang, Yirong; Tang, Guoji (Topological Methods in Nonlinear Analysis, 2025)
The purpose of this paper is to investigate the Levitin-Polyak well-posedness by perturbations of the bilevel mixed vector variational inequality (in short, BMVVI). Under suitable conditions, we prove that the Levitin-Polyak well-posedness by perturbations of the BMVVI is equivalent to existence and uniqueness of its solution and the generalized Levitin-Polyak well-posedness by perturbations of the BMVVI is equivalent to the nonemptiness and boundedness of the solution set.